Bahasa Inggris - Salsabila, Miftah; Afriana, Afriana (Universitas Putera Batam, 2025)
This research aims to analyze the journey of the main character, Scarlett, in Caraval by Stephanie Garber using Joseph Campbell’s Hero’s Journey theory. It focuses on identifying the stages present in the novel and how they contribute to Scarlett’s character development. This research applies to Joseph Campbell’s (2020) Hero’s Journey theory. The primary data source is Caraval, a fantasy novel by Stephanie Garber. This research employs a descriptive qualitative method, as defined by Litosseliti (2010) and Bogdan & Biklen (2007), which focuses on analyzing textual data in depth. The data collection follows Bowen (2009) library research approach and uses Leavy (2017) highlighting technique to categorize relevant text. The analysis applies Campbell (2020) Hero’s Journey framework and follows (Ratna, 2020) descriptive interpretation method to interpret the narrative structure and character development. The findings show that thirteen out of the seventeen stages of the Hero’s Journey are reflected in Scarlett’s journey, while four stages do not appear in the story. These results indicate that Caraval partially follows the traditional Hero’s Journey structure and demonstrates how this narrative pattern can be adapted in modern fantasy literature with a female character.